Analisis Komitmen Perusahaan Terhadap Keselamatan dan Kesehatan Kerja pada Pekerjaan Ruang Terbatas di Unit Asam Fosfat Pabrik III PT X - Melzanda, Revida Nikita; Dwiyanti, Endang (Media Gizi Kesmas, 2025)
Background: In 2018, 148 workers died due to work in confined spaces. The highest number of deaths was found in tank, bin, and vat interiors work and among construction laborers. PT X has activities working in confined spaces, one of which is in the Phosphoric Acid Unit Plant III. The work is Cleaning Strainer Line Discharge P-2501 or the activity of cleaning phosphoric acid tanks. Objectives: To analyze the commitment implemented by the company toward the occupational safety and health of workers in confined spaces in the form of tanks, especially in the Phosphoric Acid Unit Plant III of PT X. Methods: This research was a descriptive study conducted at PT X Gresik, East Java, Indonesia using an observation method. Data analysis was conducted by comparing the procedures that have been implemented in confined space work at the Phosphoric Acid Unit of Plant III with the work instruction/procedure documents made by PT X. Results: Based on data from Hazard Identification, Risk Assessment, and Determining Control (HIRADC), it was known that the potential hazards in the cleaning strainer line discharge P-2501 included high-risk work and had the impact of death. The results of gas measurements in the phosphoric acid tank in the Phosphoric Acid Unit of Plant III show that the confined space used for the cleaning strainer line discharge P-2501 activity was stated to be safe to enter and work in because oxygen (O2) was at a concentration of 20.9%, which is still in accordance with the threshold limit value (TLV) of 19.5%-23.5% and the concentration of phosphoric acid gas (HF) was still below the TLV (0.5 ppm), which is 0.0 ppm. Conclusion: The implementation and commitment of PT X to occupational safety and health for workers in confined spaces in the form of phosphoric acid tanks in the Phosphoric Acid Unit of Plant III has been carried out properly and in accordance with the work instruction documents created and owned by the company. PT X has also carried out risk control against potential hazards in confined space work in accordance with the risk control hierarchy.